PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN TIKET PESAWAT - Wiryawan Suputra Gumi; Ni Wayan Risty Deviana (STIMI Handayani Denpasar, 2020)
The aviation industry plays an essential role in the era of globalization, because it provides access to international trade, facilitates global markets and means of supporting tourism activities. This study aims to determine how much influence the marketing mix has on the decision to purchase Garuda Indonesia aeroplane tickets at I Gusti Ngurah Rai Airport, Denpasar. The method used is quantitative with primary data obtained through observation, questionnaires and literature studies using a Likert scale with a sample size of 50 respondents. The analytical method used is multiple linear regression (multilinear regression) and the classical assumption method in which analyzed with the help of SPSS application processing media version 25.0. The results showed that the Place (PC) and People (PL) variables had a positive and significant influence on purchasing decisions of all the independent variables (Product (PT), Price (PR), Place (PC), Promotion (PO), People (PL), Process (PS) and Physical Evidence (PE)) have a 34% influence on purchasing decisions.